Polarization Properties of Obliquely Incident EM Waves in Nonuniform Weakly Ionized Dusty Plasma - Li-Ping Gan; Li-Xin Guo; Jiang-Ting Li; Lin-Jing Guo (International Journal of Antennas and Propagation)
Effects of nonuniform weakly ionized dusty plasma on the polarization properties of obliquely incident electromagnetic (EM) waves were theoretically investigated in this paper. The dielectric coefficient of magnetized dusty plasma is obtained based on the Bhatnagar–Gross–Krook collision model. Then, the effects of external magnetic field, dust radii, and density on the polarization mismatch loss of obliquely incident EM waves in the L-band were analyzed using the equivalent impedance method. Results indicate that the larger the external magnetic field, the greater the polarization mismatch loss. In addition, we also found that dusty particles alleviate the deterioration of the polarization state significantly; regulating and controlling dust radius and density can avoid polarization reversal and reduce the polarization mismatch loss. We further analyzed the variation of the polarization state under different reentry heights. Our analysis reveals interesting features concerning polarization properties of obliquely incident EM waves, which provide an important theoretical basis for information reception in the plasma sheath containing ablative particles.